Fetal cardiac findings and hemodynamic changes associated with severe lower urinary tract obstruction in utero. (4th November 2019) - Cohen, J.; Levasseur, S.; Simpson, L.; Miller, R.; Freud, L.
ABSTRACT: Objectives: To describe fetal echocardiographic findings associated with lower urinary tract obstruction (LUTO) and to compare anatomic and hemodynamic measurements between fetuses with LUTO and gestational age (GA)‐matched controls, with an emphasis on quantitative indices of diastolic function and cardiac output. Methods: This was a retrospective cohort study of fetuses diagnosed with severe LUTO with giant bladder, which underwent at least one fetal echocardiogram at our center between January 2005 and June 2018. Fetuses with major congenital heart disease were excluded. Control fetuses did not have any structural or functional abnormalities and were GA‐matched to the LUTO fetuses based on the time of the first fetal echocardiogram. Cardiac anatomy and hemodynamic measurements were compared between fetuses with LUTO and controls. In infants with LUTO, serial fetal and postnatal echocardiographic data were assessed, when available, and clinical outcomes were reviewed. Results: Twenty‐six fetuses with LUTO and at least one fetal echocardiogram available were identified, one of which was excluded due to hypoplastic left heart syndrome, leaving 25 LUTO fetuses in the final cohort. The mean GA at the first fetal echocardiogram was 25.4 ± 5.1 weeks in the LUTO group and 25.3 ± 5.0 weeks in the control group. Common findings in fetuses with LUTO included cardiomegaly (40%), pericardial effusion (44%), right ventricular (RV) hypertrophy (64%) and left ventricular (LV) hypertrophy (48%). Compared with GA‐matched controls, LUTO fetuses had lower ascending aorta Z ‐score (−0.10 ± 0.94 vs −0.93 ± 1.03; P = 0.02) and aortic isthmus Z ‐score (−0.14 ± 0.86 vs −1.62 ± 1.11; P < 0.001), shorter mitral valve inflow time indexed to cardiac cycle length (0.46 ± 0.04 vs 0.41 ± 0.06; P = 0.002), and worse (increased) LV myocardial performance index (0.39 ± 0.03 vs 0.44 ± 0.04; P < 0.001). In addition, the ratio of RV to LV cardiac index was higher in LUTO fetuses compared with controls (1.62 ± 0.13 vs 1.33 ± 0.11; P < 0.001). Of the 25 LUTO pregnancies, two were lost to follow‐up, three underwent elective termination of pregnancy and three ended in intrauterine fetal demise. Four (16%) patients had mildly hypoplastic left‐heart structures, comprising two with aortic arch hypoplasia and two with mitral and aortic stenosis. Conclusion: In addition to presenting with cardiomegaly, pericardial effusion and ventricular hypertrophy, fetuses with LUTO demonstrate LV diastolic dysfunction and appear to redistribute cardiac output as compared to control fetuses, which may contribute to the development of left‐heart hypoplasia. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.